Landskapsplanering ur ett hållbarhetsperspektiv - Hermansson, Hanna (2007)
Environmental problems are accelerating with energy consumption and the release of greenhouse gases as the major issues. This affects landscape planning mostly through environmentally hazardous transportation and heating of buildings. In environmental work, the term "Sustainable development" is often used. This term was coined in the Bruntland report in 1987. A number of frameworks have been developed to clarify the term and to remind the user about relevant aspects of sustainability.